The Development of Contextual Learning-Based Big Books on the Science Literacy Ability of Grade V Elementary School Students: Pengembangan Big Book Berbasis Contextual Learning Terhadap Kemampuan Literasi Sains Siswa Kelas V Sekolah Dasar - Puspita, Ari Metalin Ika (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to produce an effective and valid contextual learning-based big book used to improve the science literacy skills of grade V elementary school students. This type of research uses Research and Development (RnD) using the ADDIE model. The subjects in this study were grade V students of SDN 2 Gamping, SDN 2 Suruh, and SDN 2 Karangsoko. The data collection technique in this study is a test. The research instruments used include observations, interviews, prototype assessments, expert validation, and science literation ability tests. Contextual learning-based big books are declared valid for use through expert test validation. The test results of teaching materials, materials, languages, and practitioners obtained an average of 92.93%, which is very valid. The results of the application of big books in small-scale and field-scale tests have an increase in the average science literacy ability of students before and after the use of big books. The results of the hypothesis test obtained a significance of 0.000 (< 0.05) that there was an increase in the average science literacy ability of students before and after the use of big books. so that contextual learning-based big books meet the categories of valid, practical, interesting, and can improve the science literacy skills of elementary school student.